Process validation of Amoxicillin and Clavulanic acid - Sandhya chaurasia, Hemendra Kumar Sharma, Nishi Prakash Jain, Anshuli Sharma (Journal of Applied Pharmaceutical Science)
As per requirement of Export Order, validation of product should be performed as per guideline. The protocol describes the process stages, control with justification, sampling plan, acceptance criteria, summary & conclusion. During validation samples with draw according to sampling plan. The Manufacturing of Amoxicillin and Clavulanic acid are validated successfully. All the data and inprocess derived during process validation of Amoxicillin and Clavulanic acid are complied with technical manufacturing document. Hence process is validated.
Keywords: Amoxicillin, Clavulanic acid, GMP, Process validation.